Separating the superradiant emission from the Hawking radiation from a rotating black hole - De-Chang Dai; Dejan Stojkovic (Physics Letters B, 2023)
Emission of particles created in the background of a rotating black hole can be greatly amplified taking away rotational energy of a black hole. This amplification affects both particles created near the horizon (due to the Hawing effect), and particles created near the potential barrier far from the horizon. Only the latter effect is called the superradiance in the strict sense. We explicitly calculate the superradiant emission for scalar particles and compare it with the total scalar particle emission (Hawking radiation plus superradiance) to clarify some confusion in the literature. We clearly show that these two emissions are not the same. In particular, superradiance persists even for extremal black holes whose Hawking temperature is zero.